Long term pulmonary morbidity after esophageal atresia and tracheoesophageal fistula repair - Burjonrappa, Sathyaprasad (Journal of Neonatal Surgery, 2021)
Background: Respiratory morbidity can influence a patient's quality of life after successful EA/TEF (Esophageal Atresia with and without Tracheo-Esophageal Fistula) repair. Multidisciplinary clinics have made it easier to manage comorbidities in patients with complex congenital malformations. The aim of this study was to evaluate the impact of respiratory issues after EA/TEF repair. Secondarily we sought to evaluate the contribution of respiratory symptoms by Broncho-Pulmonary Dysplasia (BPD) and Gastro-Esophageal-Reflux-Disease (GERD) in patients with EA/TEF. Methods: Retrospective review of the medical record of 50 patients, who underwent EA/TEF repair, needing hospital readmission for pulmonary morbidity, and subsequently followed up in a surgical clinic was performed. The data collected included patient demographics, presence and nature of significant respiratory comorbidity, findings on imaging studies and bronchoscopy, and results of pulmonary function tests (PFT). Results: Respiratory issues were identified in 75% of the patients. Congenital malformations and tracheomalacia were found in n=7 (14%) of cases. Prematurity associated BPD and Gastro-Esophageal Reflux were not the major cause of respiratory symptoms. Respiratory morbidity in this population included recurrent pneumonia n=18 (36%), reactive airway disease n=16 (32%), bronchiolitis n=4 (8%), bronchiectasis n=2 (4%), laryngitis n=2 (4%) and empyema n=1 (2%). Conclusions: Pulmonary complications significantly impact the quality of life in terms of respiratory events, after successful EA/TEF repair. While GERD is common in surgically repaired EA/TEF patients, its exact role in precipitating pulmonary morbidity needs further study. Tracheomalacia can be managed conservatively without resorting to aortopexy.